The Physiological Nutrition Basis Of The Cotton Plant With Macro - And Microfertilizers - Rozikova Kamola Elmurodovna, Sanakulov Akmal Lapasovich (International Journal of Advanced Science and Technology, 2020)
The article describes the effect of macro-and micro-fertilizers on the transpiration rate of the cotton, on the water-retaining ability of cotton leaves, on plastid pigments of leaves, including chlorophyll pigments "a" and "b", and on carotenoids. It has been studied that one of the important physiological characteristics of the plant is the transpiration rate, which changes during the day, as in the phases of its development according to the studied options. The highest transpiration rate was observed in the flowering phase of the plant at 2 p.m., as well as in cotton, the planted seeds of which were soaked with a solution of microelements of boron and manganese, feeding these solutions from leaves. If the seeds are sown after treatment with a 0.05% solution of boron and a 0.1% solution of manganese, then the ability to accumulate water in the initial phases of cotton is clearly manifested. At the subsequent stages of development, if this indicator is gradually reduced in the same way as in the control variant without fertilizers, the ability to store water is increased by an average of 3-5% during the development period by reducing the evaporation of water from leaves soaked in microfertilizers solutions. The number of plastid pigments of cotton increases to the flowering phase of the plant and decreases in subsequent periods. The amount of chlorophyll pigment "a" is 3-4 times higher than the amount of chlorophyll pigment "b", the formation of which is significantly influenced by macro-and micronutrient fertilizers. If the seeds are sown by treating them with a micro-fertilizer solution, its effect will initially be noticeable at first and decrease without any fluctuations as well as remain at the level of indicators in the background.